Reduced-order switched UIO design for switched discrete-time descriptor systems. (November 2018) - Guo, Shenghui; Zhu, Fanglai; Jiang, Bin
Abstract: In this paper, a reduced-order switched unknown input observer design is investigated for switched discrete-time descriptor systems. By a series of equivalent transformations, the original descriptor system with unknown inputs is transformed into a reduced-order standard system without unknown inputs, and then a switched reduced-order unknown input observer is designed by using standard switched system stability analysis techniques. Besides, the sufficient condition for the existence of the switched observer is also discussed in detail. Moreover, based on the state estimation, a delayed unknown input reconstruction method is also proposed. Finally, two simulation examples are given to show the effectiveness of the proposed methods.